Multilocus Sequence Typing of Pasturella multocida Isolates from Different Animal Species - Mistry, Sneha J.; Bhanderi, Bharat B.; Roy, Ashish; Mathakiya, Rafiyuddin A.; Jhala, Mayurdhvaj K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was carried out to characterize six Pasteurella multocida isolates obtained from sheep, duck, pig, cow, poultry, andP. multocida P52 vaccine strain by multilocus sequence typing (MLST). All the isolates were first confirmed positive for P. multocida byculturally first and then by a biochemical method. The Deoxyribonucleic acid (DNAs) were extracted from the isolates and PM-PCRwas carried out, which confirmed all the isolates as P. multocida, and further studied for capsular typing. Among them three isolates ofP. multocida were typed as capsular type A (sheep, duck and poultry), and the other two were typed as capsular type B (cow and pig).Specific primers and protocols described in the Rural Industries Research and Development Corporation (RIRDC) MLST scheme for P.multocida were used to amplify the seven house-keeping genes, viz., adk, est, pmi, zwf, mdh, gdh, and pgi. The purified PCR productswere subjected to sequencing by Sanger's method. The total length sequences of genes were trimmed to the length of 466 bp, 535 bp,602 bp, 500 bp, 521 bp, 530 bp, and 560 bp for adk, est, pmi, zwf, mdh, gdh and pgi genes, respectively, as described in the RIRDC MLSTscheme. Isolates of sheep, duck, pig, cattle, poultry, PAS-506/06, PAD-914/11, PAP-721/09, PAC-93/15, PAP-87/13 and P52 vaccine strainwere grouped to sequence type 122, 307, 308, 309, 129 and 122, respectively.
Keywords: Multilocus sequence typing (MLST); Pasteurella multocida; PM-PCR